Transcription-Replication Conflict Orientation Modulates R-Loop Levels and Activates Distinct DNA Damage Responses - Hamperl, Stephan; Bocek, Michael J; Saldivar, Joshua C; Swigut, Tomek; Cimprich, Karlene A (Cell, 2017)
Conflicts between transcription and replication are a potent source of DNA damage. Co-transcriptional R-loops could aggravate such conflicts by creating an additional barrier to replication fork progression. Here, we use a defined episomal system to investigate how conflict orientation and R-loop formation influence genome stability in human cells. R-loops, but not normal transcription complexes, induce DNA breaks and orientation-specific DNA damage responses during conflicts with replication forks. Unexpectedly, the replisome acts as an orientation-dependent regulator of R-loop levels, reducing R-loops in the co-directional (CD) orientation but promoting their formation in the head-on (HO) orientation. Replication stress and deregulated origin firing increase the number of HO collisions leading to genome-destabilizing R-loops. Our findings connect DNA replication to R-loop homeostasis and suggest a mechanistic basis for genome instability resulting from deregulated DNA replication, observed in cancer and other disease states.